Welcome to the 26th Annual Conference of the World Society of Cardiothoracic Surgery and the 17th Annual Congress of the South African Heart Association. - Kleinloog, Robert; Pecoraro, Alfonso J.K. (SA Heart Journal, 2017)
On behalf of the organising committee we would like to welcome you to the 26th Annual Conference of the World Society of Cardiothoracic Surgery. The conference is jointly hosted by the Society of Cardiothoracic Surgeons of South Africa and the South African Heart Association and will incorporate the Annual Conference of the SA Heart Association. We hope that the inclusion of both disciplines of cardiac surgery and cardiology will embellish the programme and give credence to, and embody, the concept of the Heart Team.